A Nesprin-4/kinesin-1 cargo model for nuclear positioning in cochlear outer hair cells - Taiber, Shahar; Gozlan, Oren; Cohen, Roie; Andrade, Leonardo R.; Gregory, Ellen F.; Starr, Daniel A.; Moran, Yehu; Hipp, Rebecca; Kelley, Matthew W.; Manor, Uri; Sprinzak, David; Avraham, Karen B. (Frontiers in Cell and Developmental Biology, 2022)
Nuclear positioning is important for the functionality of many cell types and is mediated by interactions of cytoskeletal elements and nucleoskeleton proteins. Nesprin proteins, part of the linker of nucleoskeleton and cytoskeleton (LINC) complex, have been shown to participate in nuclear positioning in multiple cell types. Outer hair cells (OHCs) in the inner ear are specialized sensory epithelial cells that utilize somatic electromotility to amplify auditory signals in the cochlea. Recently, Nesprin-4 (encoded by Syne4) was shown to play a crucial role in nuclear positioning in OHCs. Syne4 deficiency in humans and mice leads to mislocalization of the OHC nuclei and cell death resulting in deafness. However, it is unknown how Nesprin-4 mediates the position of the nucleus, and which other molecular components are involved in this process. Here, we show that the interaction of Nesprin-4 and the microtubule motor kinesin-1 is mediated by a conserved 4 amino-acid motif. Using in vivo AAV gene delivery, we show that this interaction is critical for nuclear positioning and hearing in mice. Nuclear mislocalization and cell death of OHCs coincide with the onset of hearing and electromotility and are solely restricted to outer, but not inner, hair cells. Likewise, the C. elegans functional homolog of Nesprin-4, UNC-83, uses a similar motif to mediate interactions between migrating nuclei and kinesin-1. Overall, our results suggest that OHCs require unique cellular machinery for proper nuclear positioning at the onset of electromotility. This machinery relies on the interaction between Nesprin-4 and kinesin-1 motors supporting a microtubule cargo model for nuclear positioning.